Proposta de aplicação para verificação do voto com tecnologia Blockchain: a abordagem de um modelo E2E verifiability para internet Voting da Estônia - Silva, Rodrigo Cardoso (2020)
The process of Internet voting (i-voting) is an emerging phenomenon in the international political scenario. The Republic of Estonia is a paradigm with the most extensive experience among the countries that have used i-voting. During the investigation, the Estonian experience proves that the i-voting system is the evolution of the democratic process in political, social, legal, and technological fields. However, the Internet voting system is susceptible to fraud and vulnerabilities, facts that undermine the system's confidence. The application for end-to-end verifiability (E2E) is only of the individual type in the i-voting system, resulting in partial transparency of the voting process for the voter. n this sense, the hypothesis found by the work is the recommendation to use public permissioned blockchain technology - adapted and customized by the Monero algorithm, to improve individual and universal verifiability in compliance with the principles disciplined by OSCE/ODIHR, such as anonymity, integrity and transparency in an election by the Internet. The research approach is not directly related to the information security aspects of Internet elections in Estonia, as the research understands that security is a set of factors that involve people, processes, and technologies. The purpose of academic research is to enhance confidence in the i-voting system with the use of blockchain technology for the new model of end-to-end verifiability electronic ballot (e-ballot) by voters, political parties, and members responsible for the Estonian electoral process